Muhammadiyah's Response to Covid-19 in Indonesia: Faith-Based Commitment - Qodir, Zuly; Jubba, Hasse; Loilatu, Mohammad Jafar (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2022)
As one of the most prominent Islamic organisations in Indonesia, Muhammadiyah has, since its establishment, contributed substantially to resolving various issues confronted by the Indonesian government and society. The emergence of the COVID-19 Pandemic is also a concern to Muhammadiyah. It may contribute to assisting the government's efforts and relieving some of the burden bore by the people. The current article aims to provide an analysis of Muhammadiyah's movement in Indonesia and its handling of the COVID-19 Pandemic by using a faith-based commitment approach in the da'wah Muhammadiyah on Education, health, and caring poverty in the jargon da'wah Amar ma'ruf nahi munkar/effort and supporting virtues and stopping the damaging. Through this approach, it is found that Muhammadiyah has contributed significantly in various fields, particularly health, necessities, education, and preventive measures, regardless of one's background of religion, ethnicity, and political affiliation. All the assistance that Muhammadiyah had given was based on a faith-based commitment that Muhammadiyah is a socio-religious organisation that has decided to take the path of socio-humanitarian da'wah as stipulated by Muhammadiyah's founding mandate. The data from Muhammadiyah COVID-19 Command Centre, Indonesian Governance and the Media from March 13, 2020, to January 2021 analysis with in Faith Base Organisation Perspective.